Childhood adversity subtypes and violence victimization and perpetration among early adolescents in Shanghai, China - Xiayun Zuo; Ziwei Zhang; Li Yan; Qiguo Lian; Chunyan Yu; Xiaowen Tu; Chaohua Lou (BMC, 2021)
Abstract Background This cross-sectional study aimed to identify adverse childhood experience (ACE) subtypes using variable- and person-centered approaches and examine the possible sex-differentiated associations with violence involvement as victim, perpetrator, and victim-perpetrator. Methods Adolescents aged 10-14 years in three junior high schools in Shanghai, China, were selected using a cluster sampling method in November and December 2017. Participants were surveyed anonymously using a computer-assisted self-interview approach via tablets. Thirteen items modified from the CDC-Kaiser ACE study were used to measure the ACEs. Results show subtypes as neglect, abuse, and household dysfunction by developing cumulative index score from the variable perspective and subgroups identified through the latent class analysis (LCA) from the person perspective. Logistic regression analyses were used to test the association between each ACE subtype and violence victimization and perpetration after adjusting for some demographic characteristics. Results A total of 1,700 participants were included in the final analysis. Approximately 1,322 (77.76 %) participants reported experiencing at least one ACE. The prevalence of neglect, abuse, and household dysfunction was 64.12 % (n = 1090), 61.29 % (n = 1042), and 18.24 % (n = 310), respectively. Three classes were identified through the LCA: low exposure to all ACEs (n = 854, 50.23 %), high exposure to emotional and physical abuse and neglect (n = 715, 42.06 %), and high exposure to all ACEs (n = 131,7.71 %). After controlling the covariates, experiencing abuse, neglect, and household dysfunction was significantly related to violence victimization (adjusted odds ratio [aOR] = 3.19, 3.29, 2.37, P < 0.001) and victim-perpetrator (aOR = 3.48, 4.41, 5.16, P < 0.001). Adolescent violence perpetration was only found to be associated with being neglected (aOR = 2.37, P = 0.003) and suffering household dysfunction (aOR = 3.25, P < 0.001). LCA revealed the cumulative effects of ACEs on adolescent violence victimization and perpetration. Sex-stratified analysis indicate that girls were more vulnerable to the negative effects of ACEs, with a higher risk of perpetration among girls exposed to distinctive subtypes or multiple ACEs. Conclusions ACEs were ubiquitous and significantly associated with an elevated risk of violence victimization and perpetration during early adolescence. Future research should examine whether these associations persist over time and the intermediating mechanism from the perspectives of individual neurodevelopment, cognition and resilience ability, and social support.